Pengembangan Soal Literasi Matematis Konten Aljabar pada Konteks Sosial dan Saintifik Kelas VIII SMP/MTs - Gandis Wulandari; M. Duskri (Program Studi Pendidikan Matematika, FSTT, Universitas Pendidikan Mandalika, 2026)
This study aims to develop reliable, valid, and mathematically literate algebra-based questions in social and scientific contexts for eighth-grade junior high school/MTs students. This is a research and development study that applied the Tessmer model, progressing through the preliminary stage, self-evaluation, prototyping (expert review, one-on-one, small group), and field testing. The results of this item development were tested in eighth-grade class 2 at SMPN 1 Banda Aceh, eighth-grade class 2 at SMPN 3 Banda Aceh, eighth-grade class 2 at SMPN 17 Banda Aceh, and eighth-grade class 1 at MTsN 1 Banda Aceh, with a total of 128 students participating in the test. The research instruments used were a validation sheet and a 15-item multiple-choice mathematical literacy test. The software used to determine reliability, validity, discriminant power, difficulty level, and distractor functionality was ITEMAN. This study successfully developed 15 test items, of which 13 were accepted with difficulty levels ranging from 0.30 to 0.70, discriminant power ≥ 0.30, and distractor functionality of at least 0.05. However, 2 items were discarded because they did not meet the established criteria. The analysis yielded a reliability value of 0.716, which falls into the high reliability category, meaning the test is suitable for assessing the extent to which students achieve the intended learning objectives. The developed items may serve as an assessment tool to support teachers in identifying students mathematical literacy